2001
DOI: 10.1309/fdhx-l92r-batq-2ge0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of E-Cadherin in Lobular and Ductal Neoplasms of the Breast and Its Biologic and Diagnostic Implications

Abstract: We studied the pattern of E-cadherin expression in 183 invasive carcinomas (100 ductal, 42 lobular, 41 with mixed ductal and lobular features) and 198 in situ carcinomas (131 ductal, 53 lobular, 14 in situ with ductal and lobular features) by immunohistochemistry. We found a highly significant correlation of E-cadherin membrane expression with the histologic phenotype of the tumors. While moderate to strong membrane expression of E-cadherin was seen in all invasive and in situ ductal carcinomas, 41 of 42 invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
164
3
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(190 citation statements)
references
References 31 publications
17
164
3
6
Order By: Relevance
“…This direct association was found to be 51% after accounting for chance agreement. While, Lipponen et al 39 demonstrated a similar direct association of E-CD expression with ER protein expression, other workers 30,40 did not observe any significant association between the two. It has been postulated that reversible down regulation of E-CD may occur by hypermethylation of the promoter region of E-CD expression.…”
Section: Discussionmentioning
confidence: 86%
“…This direct association was found to be 51% after accounting for chance agreement. While, Lipponen et al 39 demonstrated a similar direct association of E-CD expression with ER protein expression, other workers 30,40 did not observe any significant association between the two. It has been postulated that reversible down regulation of E-CD may occur by hypermethylation of the promoter region of E-CD expression.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, this study confirms and extends the findings of the previous study that has addressed the biologic features of mixed ductal and lobular tumours [1] indicating that these tumours have features between IDC and ILC. They are more likely to be steroid receptor positive and of lower grade than IDC and of younger age and higher grade than ILC patients [13,40,41]. The prognosis for mixed tumours compared to IDC or ILC is unclear and no previous studies have addressed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found E-cadherin expression in 0-45% of invasive lobular carcinomas. [59][60][61][62][63][64][65][66][67][68] In these studies no correlation with grade was made. The discrepancy in the literature with regard to the percentage of invasive lobular carcinomas expressing E-cadherin may relate to differences between the populations studied, sensitivity and specificity of the antibodies used and diagnostic variation as applied to lobular carcinomas.…”
Section: Discussionmentioning
confidence: 99%